Analisis Kompetensi Pedagogik Guru Sekolah Menengah Atas (SMA) - Irsyad Irsyad; Ilham Zamil (Pedagogi: Jurnal Ilmu Pendidikan, 2023)
This study aims to reveal the pedagogic competence of high school teachers. Based on the results of the study, it was found that the teacher's ability to carry out learning was still lacking. The teacher does not appreciate the courage and willingness of students in answering the questions given. Teachers also rarely use learning media and the methods used are also monotonous. Teachers also pay less attention to their students when learning takes place. This research includes quantitative descriptive analysis research. The population of this study were all teachers at public high schools in the city of Padang. The research sample was 67 people with the sampling technique being carried out using the Proportional Stratified Random Sampling technique. The research instrument was a questionnaire which was distributed to the research sample. Based on the results of the study it is known that 1) High School Teacher Pedagogic Competence from the aspect of understanding the characteristics of students is in the capable category. 2) The Pedagogic Competence of High School Teachers from the aspect of understanding learning theory and educational principles of learning is in the underprivileged category. 3) The Pedagogic Competence of High School Teachers from the aspect of ability in developing the curriculum is in the capable category. This proves that the analysis of the pedagogic competence of high school teachers is already capable, but still needs to be improved in the future.